Animal sacrifices : religious perspectives on the use of animals in science - Regan, Tom (Ethics and action, 1986)
Religions and the rights of animals / John Bowker -- The use of animals in science / Sidney Gendin -- Judaism and animal experimentation / J. David Bleich -- The place of animals in creation / Andrew Linzey -- The relevance of animal experimentation to Roman Catholic ethical methodology / James Gaffney -- Animal experimentation / Al-Hafiz B.A. Masri -- Hindu perpectives on the use of animals in science / Basant K. Lal -- Non-injury to animals / Christopher Chapple -- Of animals and man / Rodney L. Taylor.